Internal load of male varsity ice hockey players during training and games throughout an entire season - Bigg, J. L.; Gamble, A. S. D.; Spriet, L. L. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The purpose of this study was to quantify the internal load of male varsity ice hockey players, using both sessional rating of perceived exertion (sRPE) and the heart rate-derived physiological measure of training impulse (TRIMP), during training sessions and competitions throughout an entire season.